EFEKTIVITAS SISTEM PENGENDALIAN INTERN PADA KINERJA INSTANSI PEMERINTAH DI DINAS PENDAPATAN DAERAH KABUPATEN MINAHASA SELATAN - Suak, Victor Youbert Stenly; Morasa, Jenny; Rondonuwu, Sintje (Universitas Sam Ratulangi, 2018)
In a government organization requires the existence of an internal control system because with the existence ofÂ an internal control system, activities carried out by government agencies are more directed and avoid fraud and safe guard the companyâ€™s assets from irresponsible parties. The object in this study is the Regional Revenue Service of South Minahasa Regency. The purpose of this study is to analyze the effectiveness of the internal control system on the performance of government agencies in the Regional Revenue Service of South Minahasa Regency. The research method used is descriptive qualitative. Results of research internal control systems applied Government Institution in Regional tax and Retribution Management Agency of South Minahasa Regency are less effective. The achievement of Revenues and realization of Regions in 2016 is less effective because the regional Tax and Retribution Management Agency was only formed in early 2016.Keywords: Effectiveness, Internal Control